Women's Struggle Against Islamophobia In The Novel Faith And The City By Hanum Salsabiela Rais: A Spivak's Post-Colonial Analysis - Risma Nur Rahmawati (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
Westerners’ representation of east world has been done since occupation time in many Eastern areas. Although territorially eastern nations have been independent but viewed from mindset, western nations are still in control until today. Speaking of eastern nations is inseparable from Islam religion because Islam is one out of the five big religions in eastern hemisphere.  Western nations’ othering against eastern ones is also done against Muslim usually associated with East (Islam). In Indonesia, Islamic-themed works began to be accepted around 2000s. It is inseparable from the change of post-reform political structure. Journalists and writers have freedom to express idea and thought, among others, about Islam dynamic in Indonesia and the world. One of Islamic-themed works interesting to study is a novel entitled Faith and City. This novel tells about a character named Hanum and his husband named Rangga who travel to New York. A problem arises when Hanum work in GN TV that should cover Islamic life in an appropriate way. Islam is often represented as terroristic and frightening religion that supports polygamy. This research wants to find out the forms of Westerners’ othering against Easterners or Orientalists in the context of Islamophobia, particularly against women. Islamophobia is an unfounded fear of Muslim. In addition, this research wants to find out the women’s resistance in Islamophobia discussed by Westerners. This study is a qualitative research interpreting words, dialogues, and written sentences and behavior of characters observable in the text. The material object of research is Novel entitled Faith and The City by Hanum Salsabiela Rais. Meanwhile, the formal object is discriminative treatment by Westerners against subaltern women in Islamophobia discourse. The result of current research reveals that the form of oppression against women is verbal abuse shown in the media. Westerners portray Muslim life by exploiting it an inappropriate way.   Meanwhile, women’s resistance is represented by character Hanum deciding to resign from the television media that exploits Muslim life in the West.